Penerapan Pendekatan Joyful Learning untuk Meningkatkan Minat Belajar Ngaji Iqro di Kelas Rendah di SD Islam Trunojoyo - Setiarawati, Setiarawati (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
This study aims to examine how the implementation of the Joyful Learning approach can increase students’ interest in learning Iqro recitation among first-grade students at SD Islam Trunojoyo. By applying an enjoyable learning approach, data were collected through observation, interviews, and documentation during the Iqro learning activities. The results show that the use of learning methods involving interactive activities, educational games, and varied learning tasks is able to create a more positive and engaging learning atmosphere for students. Through the Joyful Learning strategy, students become more enthusiastic, more confident in trying to read Hijaiyah letters, and show increased attention during Iqro lessons. This approach also demonstrates that a comfortable and enjoyable learning environment positively influences children’s motivation to actively participate in religious learning. Therefore, Iqro learning in the first grade at SD Islam Trunojoyo can be conducted more effectively and provides meaningful learning experiences for students.